Lower limb musculoskeletal stiffness can predict overuse injuries in high level adolescent female athletes - Moresi, M.; Bradshaw, E.; Greene, D.; Naughton, G. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
The purpose of this study was to investigate whether measures of lower limb musculoskeletal stiffness (MSS) can prospectively predict overuse injuries in adolescent female athletes. Thirty-nine athletes from high-impact sports (gymnastics and track & field) completed a series of repeat jumps on force plates at baseline and 12 months later. Sport-related injuries were tracked using a self-report questionnaire. Receiver operating characteristic (ROC) curves established the predictive ability and appropriate cut-off value of baseline MSS measures. Logistic regression based on the ROC findings showed measures of MSS were able to correctly categorise 77% (p<0.01) of the prospective overuse injuries and non-injuries reported. It was concluded that measures of lower limb MSS are good predictors of overuse injury in females involved in high- impact sports.